Presence of gallstones and the risk of cardiovascular diseases: the EPIC-Germany cohort study: - Wirth, Janine; Giuseppe, Romina di; Wientzek, Angelika; Katzke, Verena; Kloss, Manja; Kaaks, Rudolf; Boeing, Heiner; Weikert, Cornelia (European journal of preventive cardiology, 2015)
Background Gallstones are common disorders associated with several cardiovascular risk factors. Gallstone formation and atherosclerosis may share key pathways, ...